Analisis Pengaruh Training, Pengembangan SDM Dan Motivasi Terhadap Produktivitas Kerja Pegawai di PT. Optimech Engineering Batam - Sabar Rismawati; Theresia Pradiani Pradiani; Fathorrahman (Lembaga Riset Ilmiah, Yayasan Mentari Meraki Asa, 2023)
This study aims to analyze the effect of training, HR development, and motivation on employee work productivity at PT. Optimech Engineering Batam. This study used a quantitative approach with a population of 100 people. The sampling technique used a saturated sample. The data analysis technique used is multiple linear regression. The results showed that the training variable had a significant effect on employee work productivity at PT. Optimech Engineering is proven by the results of hypothesis testing where the t-count value is greater than the t-table value and the significant value is less than 0.05, the HR Development Variable has a significant effect on the Work Productivity of employees at PT. Optimech Engineering is proven by the results of hypothesis testing where the t-count value is greater than the t-table value and the significant value is less than 0.05. Furthermore, the motivational variable has a significant effect on the work productivity of employees at PT. Optimech Engineering is proven by the results of hypothesis testing where the t-count value is greater than the t-table value and the significant value is less than 0.05